62.9k views
18 votes
A curve is such that
(dy)/(dx) = 2(kx-1)^5 where k is a constant.

Given that the curve passes through points ( 0 , 1) , ( 1 , 8 ) find the equation of the curve.

A curve is such that (dy)/(dx) = 2(kx-1)^5 where k is a constant. Given that the curve-example-1
User Kerby
by
5.3k points

1 Answer

2 votes

Answer:
\displaystyle y = (1)/(9)(3x-1)^(6)+(8)/(9)\\\\

=========================================================

Step-by-step explanation:

Multiply dx on each side to move it over.

Doing so gets us to


dy = 2(kx-1)^5dx

Next, integrate both sides with respect to the dy and dx terms


dy = 2(kx-1)^5dx\\\\ \displaystyle \int dy = \int 2(kx-1)^5dx\\\\ \displaystyle y = 2\int (kx-1)^5dx\\\\

We can do a u-substitution here.

Let u = kx-1 which leads to du/dx = k which turns into
du = kdx and rearranges to
dx = (du)/(k)

So the steps continuing forward could look like


\displaystyle y = 2\int (kx-1)^5dx\\\\ \displaystyle y = 2\int u^5*(du)/(k)\\\\ \displaystyle y = (2)/(k)\int u^5du\\\\ \displaystyle y = (2)/(k)\left((1)/(5+1)u^(5+1)+C\right)\\\\ \displaystyle y = (2)/(k)\left((1)/(6)u^(6)+C\right)\\\\ \displaystyle y = (2)/(k)\left((1)/(6)(kx-1)^(6)+C\right)\\\\

Let's plug in (x,y) = (0,1) and do a bit of algebra and solve for C. We'll get some equation in terms of k on the right hand side


\displaystyle y = (2)/(k)\left((1)/(6)(kx-1)^(6)+C\right)\\\\ \displaystyle 1 = (2)/(k)\left((1)/(6)(k*0-1)^(6)+C\right)\\\\ \displaystyle 1 = (2)/(k)\left((1)/(6)+C\right)\\\\ \displaystyle k = 2\left((1)/(6)+C\right)\\\\ k = (1)/(3)+2C


3k = 1+6C\\\\ 6C = 3k-1\\\\ C = (3k-1)/(6)\\\\

Now let's plug in (x,y) = (1,8) along with that C value. Then solve for k to get an actual number.


\displaystyle y = (2)/(k)\left((1)/(6)(kx-1)^(6)+C\right)\\\\ 8 = (2)/(k)\left((1)/(6)(k*1-1)^(6)+(3k-1)/(6)\right)\\\\

I'm skipping a bunch of steps, but you should get to
k = 3 when solving that equation. You can use a graphing calculator to find the root of that function (think of k as the input x) and the x intercept is 3.

This leads to,


C = (3k-1)/(6)\\\\ C = (3*3-1)/(6)\\\\ C = (8)/(6)\\\\ C = (4)/(3)\\\\

Therefore,


\displaystyle y = (2)/(k)\left((1)/(6)(kx-1)^(6)+C\right)\\\\ y = (2)/(3)\left((1)/(6)(3x-1)^(6)+(4)/(3)\right)\\\\ \boldsymbol{y = (1)/(9)(3x-1)^(6)+(8)/(9)} \ \textbf{ which is the final answer}\\\\

If k = 3, then,


\displaystyle (dy)/(dx) = 2(kx-1)^5\\\\ \displaystyle (dy)/(dx) = 2(3x-1)^5\\\\

If you were to differentiate the answer function with respect to x, then you should get the dy/dx expression mentioned.

User Mohammad Tanveer
by
5.3k points